Development of Social Entrepreneurship in Students of 5-9 Classes through Activities Outside the Classroom - Isakovna, Latipova Nigoraxon (European Journal of Life Safety and Stability (2660-9630), 2022)
The humanity of a person is determined by his spiritual and moral purity of heart, honesty, integrity. This article presents some methods for increasing the social initiative of schoolchildren through extracurricular activities.